Improving expectations regarding aging in younger adults: a classroom study. Issue 12 (1st December 2020) - Whatley, Mary C.; Castel, Alan D.
ABSTRACT: Younger adults generally hold negative attitudes and stereotypes about aging, which can affect the success with which they age as well as how they interact with older generations in everyday settings. The current study sought to improve expectations about aging in a largely first-year undergraduate student population through a small, discussion-based course on successful aging. Students in the successful aging course and a control course completed the 12-item expectations regarding aging (ERA) scale at the beginning and the end of the 10-week academic quarter. Students in the aging class also provided adjectives that came to mind when thinking about older adults. Students in the successful aging course had higher ERA scores at the end of the quarter than at the beginning of the quarter, but scores in the control class did not change. Further analyses indicated students' expectations about cognitive functioning and physical health improved, but not expectations about mental health. In addition, self-generated adjectives were more positive at the end than the beginning of the quarter, but some negative adjectives persisted. Thus, a smaller, discussion-based class about aging led to a more positive view of aging, suggesting that negative attitudes about aging may be modifiable by a short intervention in early adulthood. These results can have implications for how younger adults interact with older adults and how they may prepare for, hold future expectations about, and ultimately experience older age.